Collaboratively reimagining teaching and learning - Flora, Fabian; Jonathan, Harle; Kalimasi, Perpetua; Kilonzo, Rehema; Lamaro, Gloria; Luswata, Albert; David, Monk; Ngowi, Edwin; Nzegwu, Femi; Sikalieh, Damary (Teaching and Learning Futures, 2023)
In 2020, the African Regional Forum on Sustainable Development proclaimed Africa would only attain the Sustainable Development Goals (SDGs) if “universities in Africa collaborate in research, teaching and community or societal engagement” (Ligami, 2020). In 2022, the UNESCO World Higher Education conference called on universities to “reshape ideas and practices in higher education to ensure sustainable development for the planet and humanity” (UNESCO, 2022). While there are regular calls for African universities to improve their teaching, finding ways to do this within the resources and the available time in already stretched institutions, at the scale required, have proven elusive. This chapter is a reflexive exercise, discussing the work of an international partnership, Transforming Employability for Social Change in East Africa (TESCEA), that aimed to reshape habits of teaching and learning in institutions of higher education. We, as TESCEA partners and authors of this chapter, hope that our example can make a significan contribution towards understanding how change can happen in higher education, and particularly in resource-constrained settings. We begin by presenting our approach and then offer reflections on the change we observed, the ways in which this was achieved, and the challenges we encountered along the way